2006
DOI: 10.1111/j.1540-8167.2006.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic and Asymptomatic Atrial Fibrillation in Patients Undergoing Radiofrequency Catheter Ablation

Abstract: The results of this study demonstrate the potential utility of wireless monitoring systems in the follow-up of AF ablation patients, while also identifying poor patient compliance with an intensive monitoring protocol as an important limitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
111
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 21 publications
4
111
0
2
Order By: Relevance
“…56,57,58 It is well recognized that patients’ perception of AF varies widely. One of the first studies to examine AF symptoms prior to and following ablation found that among 114 patients who underwent 7-day Holters prior to and following ablation, 38% of the patients had only symptomatic AF episodes, 57% had both symptomatic and asymptomatic episodes, and 5% of the patients had only asymptomatic episodes.…”
Section: Section 2: Definitions Mechanisms and Rationale For Af Ablmentioning
confidence: 99%
See 1 more Smart Citation
“…56,57,58 It is well recognized that patients’ perception of AF varies widely. One of the first studies to examine AF symptoms prior to and following ablation found that among 114 patients who underwent 7-day Holters prior to and following ablation, 38% of the patients had only symptomatic AF episodes, 57% had both symptomatic and asymptomatic episodes, and 5% of the patients had only asymptomatic episodes.…”
Section: Section 2: Definitions Mechanisms and Rationale For Af Ablmentioning
confidence: 99%
“…48 In approximately half of the patients with highly symptomatic AF referred for catheter ablation, asymptomatic episodes are also present. 45,50,57,62 Arrhythmia episodes are more likely to be asymptomatic following, as compared with prior to, AF ablation. Therefore, assessment of freedom from AF postablation cannot be based on freedom from symptoms alone.…”
Section: Section 2: Definitions Mechanisms and Rationale For Af Ablmentioning
confidence: 99%
“…Significant advantages of implantable devices are the ability to perform long-term continuous monitoring and improved compliance -the latter of which can be less than 50% with prolonged ambulatory surface monitoring, even in the setting of a clinical trial. (22) The obvious disadvantages of implantable devices include cost, the need for a minimally-invasive procedure and data fatigue with an abundance of information recorded over extended periods of time.…”
Section: Interpretation Of Device-detected Atrial Tachyarrhythmiasmentioning
confidence: 99%
“…4 One of the significant limitations of external monitoring devices is that patient compliance is often quite low. 5 The CRYptogenic STroke And underLying Atrial Fibrillation (CRYSTAL AF) study 6 is presently comparing the incidence of AF among patients with cryptogenic stroke who are randomized to monitoring either with a subcutaneous device or with traditional external methods. The results of this ongoing study will begin to address the core of the question raised by Dr Willey; namely, is it better to monitor continuously for an extended period of time, even if it means possibly overlooking extremely brief episodes of AF, or is it better to monitor for much shorter durations with a technology that is capable of detecting even the briefest of episodes?…”
Section: Responsementioning
confidence: 99%